Increased IL-23R+ Th Cells Population Exhibits Higher SLEDAI-2K Scores in Systemic Lupus Erythematosus Patients - Izati, Aziz Farah; Mohd Shukri, Nur Diyana; Wan Ghazali, Wan Syamimee; Che Hussin, Che Maraina; Wong, Kah Keng (Frontiers in Immunology, 2021)
The IL-23/IL-17 axis plays causative roles in the development and progression of systemic lupus erythematosus (SLE). However, it remains unclear if the IL-17RA+ and IL-23R+ T helper (Th) cells populations are associated with serum IL-17 and IL-23 levels, or with immunological parameters and disease activities in SLE patients. Herein, we examined the proportion of IL-17RA+ and IL-23R+ Th cells, and the serum levels of IL-17 and IL-23 in established SLE patients (n=50) compared with healthy controls (n=50). The associations of these interleukins and their receptors with immunological parameters (anti-nuclear antibody [ANA], anti-dsDNA antibody, and C-reactive protein [CRP]) and SLE disease activity (SLEDAI-2K scores) in SLE patients were assessed. CD3+CD4+ Th cells of SLE patients demonstrated significantly elevated IL-17RA+ (p=1.12 x 10-4) or IL-23R+ (p=1.98 x 10-29) populations compared with healthy controls. Serum IL-17 levels were significantly lower in SLE patients compared with healthy controls (p=8.32 x 10-5), while no significant difference was observed for IL-23 serum levels between both groups. IL-23R+ Th cells population was significantly associated with higher SLEDAI-2K scores (p=0.017). In multivariate analysis, the proportion of IL-23R+ Th cells remained significantly associated with higher SLEDAI-2K scores independent of prednisolone intake (p=0.027). In contrast, serum IL-17 or IL-23 levels were not associated with immunological parameters, SLEDAI-2K scores and the proportion of IL-23R+ Th cells in SLE patients. In conclusion, our results support that therapeutic inhibition of the IL-23/IL-17 axis receptors on Th cells, particularly IL-23R, is potentially relevant in SLE patients.